CEDAW Convention and Engendering Faculty of Law's Curriculum Reinforcement: A Lesson Learnt from Indonesia - Kasuma, Iva; Irianto, Sulistyowati (UI Scholars Hub, 2023)
This research aims to describe the strategies used to eliminate discrimination against women through academic-based programs conducted in universities. This includes the International Law, a powerful reference for teaching material in legal education used to promote humanity. Presently, globalization of law is marked in the International Law-making process by delegates from various countries, which spreads to State parties through ratification with a significant impact on legal reform. A number of senior female professors have initiated the socialization and implementation of the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW Convention). This was conducted through the ratification of Law No. 7 of 1984, which has been continued by the younger scholars. The establishment of the Convention Watch Working Group of Universitas Indonesia is a fame of light for academics to accomplish their duties to educate and literate law students, legal practitioners, law enforcers, and the wider communities. The process of promoting the CEDAW Convention and strengthening gender equality has been spread to many universities in Indonesia within 30 years, mainly through the program of Engendering Faculties of Law's Curriculum. Presently, no fewer than 75 law faculties in Indonesia provide a lecture on